Effectiveness of direct‐acting agents for chronic hepatitis C treatment in South America: A systematic review and meta‐analysis. Issue 12 (5th August 2020) - Castro Filho, Elio C.; Piedade, Juliana; Castro, Rodolfo; Luz, Paula M.; Fernandes, Flavia; Grinsztejn, Beatriz; Veloso, Valdilea G.; Pereira, Gustavo Henrique; Perazzo, Hugo
Abstract: The effectiveness of direct‐acting agents (DAAs) for hepatitis C treatment in limited‐resource settings remains unclear. We estimated the pooled sustained virological response rates of DAA therapy in South America. We searched online databases for studies that reported 12‐week sustained virological response (SVR12) to hepatitis C virus (HCV) treatment in individuals living in South America. Pooled SVR12 in intention‐to‐treat (ITT) and per‐protocol were estimated. Additionally, using all studies with available data, the pooled relative risk (RR) of SVR12 using a random‐effects model (DerSimonian‐Laird) was estimated to compare effectiveness of DAAs in patients with or without cirrhosis, HIV co‐infection or previous HCV therapy. Heterogeneity was assessed using the I 2 statistics. We identified 20 studies [14 manuscripts and 6 conference abstracts] comprising 7393 individuals from five countries [Brazil (n = 11), Argentina (n = 4), Chile (n = 1), Colombia (n = 1) and Peru (n = 1)] and two South‐American collaborations. The pooled overall SVR12 rates [95% confidence interval (CI)] were 92.6% [90.2‐94.7] and 95.5% [94.3‐96.6] by ITT (11 studies; n = 4, 153; I 2 = 84.2%) and per‐protocol analysis (15 studies; n = 4, 833; I 2 = 64.5%), respectively. The RR of SVR12 was similar in patients with or without HIV co‐infection [4 studies; RR = 1.03 (0.99‐1.07)] and those naive compared with treatment experimented‐individuals [9 studies; RR = 1.01 (1.00‐1.03)], but significantly higher in patients without cirrhosis compared with those with cirrhosis [11 studies; RR = 1.04 (1.02‐1.05), P < .001]. DAAs are highly effective for HCV treatment in South America. The use of DAAs should be considered in limited‐resource settings to decrease the burden of liver disease in HCV‐infected patients. PROSPERO[CRD 42019134603].